การประเมินความสามารถของแบบจำลอง RegCM4 ในการจำลองฟลักซ์ความร้อนและลมบริเวณประเทศไทย - พิภัทรา แซ่ซิน (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
Heat fluxes and wind are essential factors to oceanic and climatic changes. This study evaluated the performance of heat flux and wind simulations over Thailand by dynamical downscaling with regional climate model, RegCM4 from 2 General Circulation Models (GCMs), EC-EARTH and MPI-ESM-MR, and investigated changes of heat fluxes and wind in the future under the Representative Concentration Pathways (RCPs), RCP 4.5 and RCP 8.5. Future projections were divided to two time periods which are near-future projections (2020-2049) and far-future projections (2070-2099). The results showed that both models overestimated shortwave radiation flux (SWR), longwave radiation flux (LWR), latent heat flux (LHF), and winds, while underestimated sensible heat flux (SHF) when compared with ERA-Interim data. MPI-ESM-MR provided simulations of heat fluxes and wind closer to the ERA-Interim data more than EC-EARTH. Results of future changes indicated that the far-future projections were the most changes of those parameters, particularly the projections under RCP 8.5. Projected decrease in net LWR was an important factor in the changes of heat balance which could arise from increasing greenhouse gases in the atmosphere. SWR trended to increase due to decreasing of cloud cover in the atmosphere. Increasing of LHF might be a result of increasing of air temperature which enhances saturated water vapor capacity. The changes of SWR, LWR and LHF resulted in increases of net heat fluxes in the far-future period under RCP 8.5 by 7-10 W/m2, and surface temperature by 3oC. There were few changes of winds in the future (~ 1 m/s). Southerly winds had more influence in southwest monsoon season, whereas, easterly winds had more influence in northeast monsoon season. The changes of heat fluxes and wind in the future might affect terrestrial and marine ecosystems via increased temperature and changes of water cycle.